Kinerja Indek Saham Syariah Yang Terdaftar Pada Jakarta Islamic Index Pasca Pengumuman Pemilu Presiden 2019 - Seviana Noor Putri Nindiah; Himawan Arif Sutanto (Journal of Economics and Business, 2020)
Event study is an activity to observe the information impact of a phenomenon on the prices of securities to observe the stock performance in this research. This study was aimed to analyze the differences in the average of abnormal return and trading volume activity before and after 10 days the election even announced the new president on May 2019. the method to determine the sample in this study is purposive sampling number from 30. The technique to analyze the data is paired sample t-test. This research finds out that there are different average abnormal returns before and after the announcement of the president election in 2019, while there is no difference in the trading volume of activity before and after the announcement of the president election.